Pengaruh regimen kombinasi transcutaneous electrical nerve stimulation (TENS) dan infra red radiation (IRR) dengan exercise therapy terhadap nyeri dan fungsional lutut pada petani penderita osteoartritis - Kurniawan, Ryanda Masri; Berawi, Khairun Nisa; Suharmanto, Suharmanto; Pramesona, , Bayu Anggileo; Saftarina, Fitria (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Osteoarthritis (OA) in farmers can cause significant functional impairment, which can be addressed with Transcutaneous Electrical Nerve Stimulation (TENS), Infrared Radiation (IRIR), and exercise therapy.Purpose: To analyze the effect of a combination of transcutaneous electrical nerve stimulation (TENS) and infrared radiation (IRIR) with exercise therapy on knee pain and function in farmers with osteoarthritis.Method: This was an experimental study with a two-group pre-test and post-test design. The study was conducted at the Karang Pucung Community Health Center, South Lampung, from May to June 2025. The study population consisted of 68 farmers with osteoarthritis, representing the total sample. Thirty-four farmers with OA received 25 minutes of exercise therapy, and 34 farmers with OA received a combination of TENS and IRIR for 30 minutes. Pain measurements before and after the intervention were conducted using the Visual Analogue Scale (VAS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Analysis used the Wilcoxon test and the Mann-Whitney test.Results: The average age of farmers in the Exercise Therapy group was 45-50 years, while in the TENS & IRR group, it was 45-50 years. In the TENS & IRR with Exercise Therapy group, there were more women with a history of osteoarthritis. In the TENS & IRR group, lesions were more common on the right side, while in the Exercise Therapy group, farmers with osteoarthritis were more common on the left side. There were differences in average knee pain and functional scores before and after administration of analgesics, a combination of Transcutaneous Electrical Nerve Stimulation (TENS) and Infrared Radiation (IRR) with Exercise Therapy given to farmers with osteoarthritis. Conclusion: There was a difference in average pain scores before and after administration of exercise therapy in the Combined Transcutaneous Electrical Nerve Stimulation (TENS) and Infrared Radiation (IRR) group. However, there was a significant difference in the exercise group compared to the TENS & IRR group.Suggestion: Collaboration with relevant parties is recommended to organize educational programs and OA management for farmers using analgesics and exercise therapy. Keywords: Exercise Therapy; Farmers; Functional Knee; Infrared Radiation (IRR); Osteoarthritis Patients; Pain; Transcutaneous Electrical Nerve Stimulation (TENS). Pendahuluan: Osteoartritis (OA) pada petani dapat menyebabkan gangguan fungsional yang signifikan, hal ini dapat diatasi dengan menggunakan Transcutaneous Electrical Nerve Stimulation (TENS), Infra Red Radiation (IRR) dan exercise therapy. Tujuan: Untuk menganalisis pengaruh regimen kombinasi transcutaneous electrical nerve stimulation (TENS) dan infra red radiation (IRR) dengan exercise therapy terhadap nyeri dan fungsional lutut pada petani penderita osteoartritis. Metode: Jenis penelitian ini eksperimental menggunakan pre and post test two group design. Penelitian ini dilakukan di wilayah kerja Puskesmas Karang Pucung Lampung Selatan pada bulan Mei-Juni 2025. Populasi penelitian adalah petani penderita osteoatrritis sebanyak 68 petani OA dengan total sampling. 34 petani OA diberikan exercise therapy selama 25 menit dan 34 petani OA diberikan kombinasi TENS dan IRR selama 30 menit. Pengukuran sebelum dan setelah intervensi menggunakan skala nyeri menggunakan Visual Analogue Scale (VAS) dan Western Ontario and Mcmaster Universities Osteoarthritis Index (WOMAC). Analisis menggunakan Wilcoxon test dan Mann Whitney test. Hasil: Mayoritas petani pada kelompok Exercise Therapy berusia rata – rata 45-50 tahun, sedangkan untuk kelompok TENS & IRR berusia 45-50 tahun. Pada kelompok TENS & IRR dengan Exercise Therapy, lebih banyak berjenis kelamin perempuan yang memeiliki riwayat penyakit osteoarthritis. Pada kelompok TENS & IRR lebih banyak pada lesi kanan, sedangkan pada kelompok Exercise Therapy petani mereka yang menderita osteoarthritis lebih banyak terkena pada lesi kiri. Ada tingkat rerata skor nyeri dan fungsional lutut sebelum dan sesudah diberikan Analgesik, Kombinasi Transcutaneous Electrical Nerve Stimulation (TENS) dan Infra Red Radiation (IRR) dengan Exercise Therapy pada petani penderita Osteoarthritis. Simpulan: Terdapat perbedaan skor rata-rata nyeri sebelum dan sesudah diberikan pada kelompok Kombinasi Transcutaneous Electrical Nerve Stimulation (TENS) dan Infra Red Radiation (IRR) dengan Exercise Therapy. Namun, pada kelompok Exercise terlihat selisih yang signifikan dari pada kelompok TENS & IRR. Saran: Agar menjalin kerjasama dengan pihak terkait untuk menyelenggarakan program edukasi dan penanganan OA pada petani menggunakan tindakan analgesik dan exercise therapy. Kata Kunci: Exercise Therapy; Fungsional Lutut; Infra Red Radiation (IRR); Nyeri; Penderita Osteoartritis; Petani; Transcutaneous Electrical Nerve Stimulation (TENS).